(1S, 3R, 4S, 5R)5-O-Caffeoylquinic acid: Isolation, stereo-structure characterization and biological activity. (1st July 2015) - Forino, Martino; Tenore, Gian Carlo; Tartaglione, Luciana; Carmela, Dell'Aversano; Novellino, Ettore; Ciminiello, Patrizia
Highlights: The chlorogenic acid stereoisomer (1 S, 3 R, 4 S, 5 R )5-O-Caffeoylquinic acid is identified. (1 S, 3 R, 4 S, 5 R )5-O-Caffeoylquinic acid is a major antioxidant in Sorbus domestica fruit. (1 S, 3 R, 4 S, 5 R )5-O-Caffeoylquinic acid reduces glucose and cholesterol uptake. Abstract: Sorbus domestica fruits (sorbs) are commonly harvested and consumed for their nutritious qualities and have long been used as natural remedy against diabetes in the popular medicine. Recently, sorbs have been described as sources of antioxidant compounds including polyphenols. Chemical analyses carried out on sorbs collected in Southern Italy have led to the isolation of a chlorogenic acid isomer as the main antioxidant compound contained in the fruit butanol extract. NMR studies have identified the isolated compound as (1 S, 3 R, 4 S, 5 R )5-O-Caffeoylquinic acid. In comparison to chlorogenic acid, the isolated isomer features an inverted configuration at C4. Such configurational inversion causes the chlorogenic acid stereoisomer acid to assume a preferential conformation remarkably different from that of chlorogenic acid. This seems to account for the enhanced potency of (1 S, 3 R, 4 S, 5 R )5-O-Caffeoylquinic acid to reduce both the glucose and cholesterol uptakes by the cell line HepG2 when compared to chlorogenic acid.